SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PENGURUS OSIS MENGGUNAKAN METODE FUZZY TSUKAMOTO: Metode Fuzzy Tsukamoto - M. Asep Thosin; Purnomo Hadi Susilo; Agus Setia Budi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The selection process of Student Council (OSIS) administrators is commonly conducted manually, which may lead to bias and inconsistency in decision-making. This study aims to develop a web-based Decision Support System (DSS) using the Fuzzy Tsukamoto method to provide a more objective and measurable recommendation for selecting OSIS members. The research employed the Research and Development (R&D) approach following the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The assessment of prospective OSIS members was based on six criteria: academic performance, leadership, discipline, responsibility, communication skills, and achievements in academic olympiads. The Fuzzy Tsukamoto method was implemented through fuzzification, rule-based inference, and defuzzification processes to generate final scores and rankings for each candidate. The system was tested using data from 220 prospective OSIS members. Performance evaluation was conducted by comparing the system's recommendations with the supervisor's decisions using a Confusion Matrix. The results indicate that the system is capable of producing consistent and objective candidate rankings while supporting a more effective, transparent, and accurate selection process. The implementation of a web-based DSS utilizing the Fuzzy Tsukamoto method has proven to assist decision-makers in selecting qualified OSIS members according to predefined criteria and improving the overall quality of the selection process in schools. Keywords: Decision Support System, Fuzzy Tsukamoto, Student Council (OSIS), Web-Based DSS, Confusion Matrix.